Self-Reported Oral Hygiene Performance of Patients in Albania: A Questionnaire-Based Survey - Blerina Zeza; Blerina Osmani; Erdita Cenameri; Busra Emir (Dentistry Journal)
Background/Objectives: Oral hygiene is a key factor for dental and periodontal diseases and the prognosis of any treatment to restore their consequences. The present survey aimed to evaluate how well informed patients in Albania are on oral hygiene, given the scarce evidence on this topic. Methods: This survey was performed using a Google Forms questionnaire on oral hygiene habits, type and technique of instruments used, and frequency of dental recall visits. Results: A total of 1006 questionnaires were filled in a one-month time period (January 2020) from a population of 75.2% females and 24.8% males, 32.7 ± 11.3 years of age, from whom 94.6% reported a lack of systemic diseases and 80% were non-smokers. All of the population brushed their teeth at least once daily. The most used type of toothbrush was a manual one (91.1%) with medium-bristle hardness in 71% of cases. The most prevalent way of using the toothbrush was through circular movements (36.7%) with a duration of 2–3 min in 72% of the population. Only 77.1% of the population used interdental instruments, mainly interdental floss. Conclusions: Within the limits of this study, it could be concluded that the present population seemed to be mostly appropriately informed, but the information needs further revision and promotion by dentists.